Rendahnya literasi pada mahasiswa pendidikan bahasa Arab - Sofi, Utari Nur (Maliki Interdisciplinary Journal, 2024)
This research was motivated by the low interest of students in reading books so that students' knowledge was included in the deficient category. This is proven by the facts found in the field, including, students' minimal knowledge regarding the material in lectures, the lack of handbooks they own, and when they have handbooks students do not read them with focus. Especially Arabic language education students who really need a lot of knowledge about various branches of science to support complete learning. The purpose of writing this article is to find out what factors hinder students' literacy progress and several solutions that will be presented to deal with this.